Evaluasi Kinerja Pelabuhan Pantoloan Kota Palu - Rumata, Nini Apriani; Idrus, Irnawaty; Amansah, Muh. Sucitra (Jurnal Karajata Engineering, 2024)
The city of Palu is located in a very strategic area which making it a gateway to connect Central Sulawesi with Kalimantan Island. Pantoloan port developed as a support for the movement but even with the strategic location and enormous potential, this port tends to be quiet with activities that should be present at ports in general. This research aims to determine the level of satisfaction of port users and to analyze the factors that influence its performance. This research using a descriptive method with qualitative approach through distributing questionnaires to respondents which later be analyzed using the Customer Satisfaction Index and Importance Performance Analysis methods. The results of the evaluation study on the performance of Pantoloan Port are that port users are quite satisfied with a percentage reaching 52%. Other factors that greatly influence the level of satisfaction and are priorities in developing port performance are timeliness, accessibility and affordable rates.